Anion exchange membrane electrolysis water oxygen evolution electrode and preparation method and application thereof
By loading catalytic materials on the high-strength porous metal carrier of the anion exchange membrane water electrolysis oxygen evolution electrode and forming a conductive layer, the problems of large contact resistance and internal resistance of existing electrodes when stacked are solved, and the effects of high catalytic activity and low overpotential are achieved.
Patent Information
- Application Number
- CN202511011341.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-22
- Publication Date
- 2025-09-16
AI Technical Summary
The existing anion exchange membrane water electrolysis oxygen evolution electrodes have large contact resistance and high internal resistance due to insufficient catalytic layer and conductivity when stacked, which in turn increases the cell voltage and reduces the current density.
A high-strength porous metal carrier is used to prepare alloy fiber felt through vacuum induction melting technology. Combined with vacuum drying and acid cleaning processes, catalytic materials are fully loaded on one side of the carrier to form a catalytic layer, and the catalytic layer on the other side is washed away to form a conductive layer.
The mechanical strength and flatness of the electrode are improved, the contact resistance and internal resistance are reduced, the catalytic activity is enhanced, the oxygen evolution overpotential is reduced, and the water electrolysis performance of the electrolyzer is improved.
Smart Images

Figure CN120649056A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalytic materials, and in particular relates to an anion exchange membrane water electrolysis oxygen evolution electrode and a preparation method and application thereof. Background Art
[0002] Anion exchange membrane water electrolysis is the third generation of water electrolysis hydrogen production technology, which has the advantages of low cost and resistance to wind and solar fluctuations. The preparation methods of the anode oxygen evolution electrode of anion exchange membrane water electrolysis include electrodeposition, hydrothermal method, and corrosion method. Regardless of which method is used, it needs to be carried out in solution. Since the carrier has a porous structure, the deposition solution will penetrate into all parts of the carrier, so a catalytic layer will be loaded on both sides of the electrode. Since the catalytic layer is composed of oxides or hydroxides, although the catalytic performance is excellent, the conductivity is poor. The water electrolysis performance is a comprehensive expression of the catalytic performance, conductive performance and mass transfer performance of the electrode. When stacking, the large contact resistance between the electrode and the bipolar plate and the large internal resistance of the electrode will lead to an increase in the cell voltage of the stack and a decrease in the current density. Summary of the Invention
[0003] In response to the deficiencies in the above-mentioned prior art, the present invention provides an anion exchange membrane water electrolysis oxygen evolution electrode and its preparation method and application. The present invention first prepares a high-strength porous metal carrier, then fully loads the catalytic material on the high-strength porous metal carrier to form a catalytic layer, then washes away the catalytic layer on one side of the high-strength porous metal carrier, and forms a conductive layer to obtain an anion exchange membrane water electrolysis oxygen evolution electrode. The anion exchange membrane water electrolysis oxygen evolution electrode prepared by the method of the present invention has the characteristics of high strength, high flatness, high conductivity and high catalytic performance. The high mechanical strength can withstand high stacking pressure and the impact pressure of the electrolyte, the high flatness reduces the contact resistance, the high conductivity reduces the internal resistance of the stack, and the high catalytic activity reduces the oxygen evolution overpotential, thereby overcoming the technical defects of the anion exchange membrane in the prior art.
[0004] Based on the above technical objectives, the present invention adopts the following technical solutions: The present invention provides a method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode, comprising the following steps: The method uses a metal mixture as raw material, and sequentially undergoes smelting, cooling, forging, rolling, cutting into alloy fibers, making into felt, high-temperature sintering, and pressing. The pressing forming conditions are: pressing at room temperature and 5Mpa~20Mpa to obtain a high-strength porous metal carrier; using vacuum induction melting technology, the metal mixture is melted and mixed evenly to form an alloy liquid with uniform composition, the alloy liquid is poured into a mold and cooled and solidified to form a casting, the casting is forged and rolled into alloy rods, the alloy rods are cut into alloy fibers, and made into felt by airflow laying, and sintered at high temperature to obtain a porous carrier, which is pressed on a calender to obtain a high-strength porous metal carrier with a smooth surface and high strength, and the high-strength porous metal carrier does not deform under a pressure of 5Mpa.
[0005] The metal mixture consists of nickel and an active metal raw material, the active metal raw material being selected from one or more of Fe, Cr, Mn, Mo, Zn, and Al. The mass percentage of nickel in the metal mixture is ≥ 95%, and the sum of the mass percentages of nickel and the active metal raw material is 100%. Nickel hydroxide readily grows on the surface of metallic nickel, but when alloyed with other metals, nickel hydroxide and other metal hydroxides do not grow on the alloy surface.
[0006] Two or more soluble metal salts are dissolved in water to obtain a mixed solution; a high-strength porous metal support is immersed in the mixed solution, and then an alkali solution is added. The high-strength porous metal support is immersed in the mixed solution and then aged with the alkali solution. The alkali solution converts the soluble metal salt into a metal hydroxide. The aging effect is to make the metal hydroxide grow sufficiently on the surface of the metal support with good crystallinity, so that the metal hydroxide is fully loaded on the high-strength porous metal support to form a catalytic layer, and the support is washed with water until neutral, and vacuum dried at a temperature of RT-100°C for 1 hour to 12 hours to obtain an electrode with a catalytic layer on both sides. The catalytic layer on one side of the electrode with a double-sided catalytic layer is cleaned with acid for 1 to 10 minutes, exposing the alloy fiber. The alloy fiber is then washed with water until neutral and vacuum dried at RT-100°C for 1 to 12 hours to obtain an anion exchange membrane water electrolysis oxygen evolution electrode. Because the alloy fiber surface does not contain catalytic material and the alloy fiber has excellent electrical conductivity, a conductive layer is formed. The acid cleaning method is as follows: After absorbing the acid with absorbent paper to saturation, one side of the electrode with a double-sided catalytic layer is laid flat on the absorbent paper, and the catalytic layer in contact with the absorbent paper is washed with acid to remove it.
[0007] Preferably, the diameter of the alloy fiber is 20 μm to 50 μm. Alloy fibers with too thin a diameter are easily broken, and alloy fibers with too thick a diameter have a small surface area and can provide fewer growth sites for the catalytic layer.
[0008] Preferably, the high temperature sintering conditions are: in a vacuum degree of 10 -3 ~10 -5 Under Pa conditions, sinter at 800℃~1200℃ for 30min~120min.
[0009] Preferably, the soluble metal salt is selected from a soluble iron salt, a soluble cobalt salt or a soluble nickel salt, wherein the iron-cobalt molar ratio is 0.5-2:2-5, the iron-nickel molar ratio is 0.5-3:5-30, the cobalt-nickel molar ratio is 2-5:5-20, the iron-cobalt-nickel molar ratio is 0.5-3:2-5:5-30, and the concentration of the soluble metal salt is 0.001 mol / L-1 mol / L; iron, cobalt and nickel all have excellent catalytic properties, and the soluble metal salt also has catalytic properties at low concentrations as long as the growth time is long enough.
[0010] Preferably, the alkali in the alkali solution is selected from one of KOH, NaOH, K2CO3, Na2CO3, KHCO3, NaHCO3, and urea, and the concentration of the alkali solution is 0.001mol / L-10mol / L; the alkali solution can be used to prepare metal hydroxides at a low concentration as long as the growth time is long enough.
[0011] Preferably, the porosity of the high-strength porous metal carrier is 50% to 70%, and the air permeability is 0.1 cm 3 / (cm 2 ·s·kPa)~5cm 3 / (cm 2 ·s·kPa), with a thickness of 0.2mm~1mm. If the thickness is too thin, the mechanical strength is insufficient and it is easy to bend; if the thickness is too thick, the air permeability is poor, which affects the mass transfer of gas and liquid during the electrolysis process, resulting in poor electrolysis performance.
[0012] Preferably, the aging condition is: standing at room temperature for 1 hour to 6 hours.
[0013] Preferably, the acid in the acid solution is selected from one or more of oxalic acid, nitric acid, hydrochloric acid, and sulfuric acid, and the pH of the acid solution is 4-5.
[0014] The present invention also provides an anion exchange membrane water electrolysis oxygen evolution electrode, which is prepared by the above preparation method.
[0015] The present invention also protects the application of an anion exchange membrane water electrolysis oxygen evolution electrode in the preparation of an anion exchange membrane electrolyzer.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention first prepares a high-strength porous metal support, then fully loads the high-strength porous metal support with a catalytic material to form a catalytic layer. The catalytic layer on one side of the high-strength porous metal support is then washed away, and a conductive layer is formed to obtain an anion exchange membrane water electrolysis oxygen evolution electrode. The high-strength porous metal support is designed by, on the one hand, using a variety of active metals to enhance the catalytic activity of the anion exchange membrane water electrolysis oxygen evolution electrode; on the other hand, the high-strength porous metal support undergoes high-intensity pressing during the molding process, which not only provides a flat surface and reduces contact resistance, but also has high mechanical strength, capable of withstanding high stacking pressure and the pressure difference between the anode and cathode of the electrolyzer.
[0017] In response to the problem in the prior art that "the design of the anion exchange membrane only contains a catalytic layer, and the catalyst coats the entire carrier. In a three-electrode system, due to the high catalyst loading, it has a low overpotential, and the performance after stacking is not necessarily optimal. This is because the voltage of the electrolytic cell chamber after stacking is affected by the combined influence of the electrode catalytic activity, conductivity, and contact resistance," the present invention designs a catalytic layer and a conductive layer. The catalytic layer is a metal hydroxide, and the catalytic layer has a flaky morphology and a high specific surface area, providing a large number of active sites for the reaction. It has good catalytic activity but poor conductivity. Based on this, the present invention washes away the catalytic layer on one side, exposing the alloy fibers, increasing the conductivity to a level close to that of pure nickel, and forming a conductive layer. Since the side in contact with the diaphragm during stacking plays the primary catalytic role, the electrode catalytic activity does not decrease substantially. The present invention improves the oxygen evolution performance of the electrolytic cell by designing a catalytic layer with a flaky structure and a metal alloy conductive layer.
[0018] 1. Compared with the prior art, the preparation method of the present invention does not require high temperature and high pressure, the preparation conditions are mild, and the catalytic layer grows uniformly, which is suitable for the preparation of large-scale anion exchange membrane water electrolysis oxygen evolution electrodes. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is an SEM image of the catalytic layer and conductive layer of the anion exchange membrane water electrolysis oxygen evolution electrode in Example 1.
[0020] Figure 2 This is a polarization curve diagram of the anion exchange membrane water electrolysis oxygen evolution electrode in the three-electrode system of Example 1.
[0021] Figure 3 In the figure, (a) is a polarization curve diagram of the anion exchange membrane water electrolysis oxygen evolution electrode in the electrolyzer of Example 1, and (b) is a polarization curve diagram of the electrode with catalytic layers on both sides in the electrolyzer of Example 1. DETAILED DESCRIPTION
[0022] To enable those skilled in the art to better understand and implement the technical solutions of the present invention, the present invention is further described below with reference to specific examples and accompanying drawings. However, the examples are not intended to limit the present invention. The following experimental and detection methods are conventional methods unless otherwise specified; the reagents and raw materials are commercially available unless otherwise specified.
[0023] The following examples and comparative examples are used to further study the technical solution of the present invention. The specific research methods and results are as follows: Example 1 A method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode comprises the following steps: S1. The metal raw materials Ni, Fe, Cr, Mn, Mo, Zn and Al are weighed in a mass ratio of 95:1:0.5:0.5:2:0.5:0.5, and then put into a vacuum induction melting furnace to melt the metals and form a uniform alloy solution. The rods are formed through solidification, forging and rolling, and then cut into alloy fibers with a diameter of 20 μm. After the alloy fibers are dispersed, they are placed in a vacuum furnace with a degree of vacuum of 10 -4 The nickel fiber felt is sintered in a sintering furnace at 1000°C for 90 minutes, and then pressed at 20 MPa at room temperature to form a high-strength porous metal carrier, namely nickel fiber felt. The nickel fiber felt has a thickness of 0.2 mm and a porosity of 60%.
[0024] S2. Dissolve 12g of ferric chloride, 8g of cobalt chloride and 45g of nickel chloride in 2L of water, stir until mixed evenly to obtain a mixed solution; use nickel fiber felt as a carrier, place the carrier in the mixed solution, add 0.1mol / L potassium hydroxide solution to the mixed solution, and let it stand to react for 2h. Then, remove the nickel fiber felt, place it in clean water for ultrasonic cleaning 3 times, and vacuum dry it to obtain an electrode with a catalytic layer on both sides.
[0025] S3. Weigh 0.0213 g of oxalic acid, dissolve it in 1 L of deionized water, and prepare an oxalic acid solution with a pH of 4. Then use absorbent paper to absorb the prepared oxalic acid solution until it is saturated. Lay one side of the electrode with a catalytic layer on the surface of the absorbent paper. After 10 minutes, wash away the catalytic layer in contact with oxalic acid to expose the alloy fiber. Then wash it with deionized water and vacuum dry it to obtain an anion exchange membrane water electrolysis and oxygen evolution electrode.
[0026] Example 2 A method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode comprises the following steps: S1. The metal raw materials Ni, Fe, Cr, Mn, Mo, Zn and Al were weighed in a mass ratio of 96:1:0.5:0.5:1:0.5:0.5, and then put into a vacuum induction melting furnace to melt the metals and form a uniform alloy solution. The rods were solidified, forged and rolled, and then cut into alloy fibers with a diameter of 30 μm. After the alloy fibers were dispersed, they were placed in a vacuum furnace with a degree of vacuum of 10 -4 The nickel fiber felt is sintered in a sintering furnace at 1000°C for 90 minutes, and then pressed at 18 MPa at room temperature to form a high-strength porous metal carrier, namely nickel fiber felt. The nickel fiber felt has a thickness of 0.4 mm and a porosity of 60%.
[0027] S2. Dissolve 12g of ferric chloride, 8g of cobalt chloride and 45g of nickel chloride in 2L of water, stir until mixed evenly to obtain a mixed solution; use nickel fiber felt as a carrier, place the carrier in the mixed solution, add 0.1mol / L potassium hydroxide solution to the mixed solution, and let it stand to react for 2h. Then, remove the nickel fiber felt, place it in clean water for ultrasonic cleaning 3 times, and vacuum dry it to obtain an electrode with a catalytic layer on both sides.
[0028] S3. Weigh 0.0213 g of oxalic acid, dissolve it in 1 L of deionized water, and prepare an oxalic acid solution with a pH of 4. Then use absorbent paper to absorb the prepared oxalic acid solution until it is saturated. Lay one side of the electrode with a catalytic layer on the surface of the absorbent paper. After 20 minutes, wash away the catalytic layer in contact with oxalic acid to expose the alloy fiber. Then wash it with deionized water and vacuum dry it to obtain an anion exchange membrane water electrolysis and oxygen evolution electrode.
[0029] Example 3 A method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode comprises the following steps: S1. The metal raw materials Ni, Fe, Cr, Mn, Mo, Zn and Al are weighed in a mass ratio of 95:1:0.5:0.5:2:0.5:0.5, and then put into a vacuum induction melting furnace to melt the metals and form a uniform alloy solution. The rods are formed through solidification, forging and rolling, and then cut into alloy fibers with a diameter of 30 μm. After the alloy fibers are dispersed, they are placed in a vacuum furnace with a degree of vacuum of 10 -5 The nickel fiber felt is sintered in a sintering furnace at 800°C for 120 minutes, and then pressed at 20 MPa at room temperature to form a high-strength porous metal carrier, namely nickel fiber felt. The nickel fiber felt has a thickness of 0.2 mm and a porosity of 60%.
[0030] S2. Dissolve 12g of ferric chloride, 8g of cobalt chloride and 45g of nickel chloride in 2L of water, stir until mixed evenly to obtain a mixed solution; use nickel fiber felt as a carrier, place the carrier in the mixed solution, add 0.1mol / L potassium hydroxide solution to the mixed solution, and let it stand to react for 2h. Then, remove the nickel fiber felt, place it in clean water for ultrasonic cleaning 3 times, and vacuum dry it to obtain an electrode with a catalytic layer on both sides.
[0031] S3. Use a pipette to measure 8.33 μL of concentrated hydrochloric acid, dilute it with deionized water, and then introduce it into a 1 L volumetric flask to make up the volume. Prepare a hydrochloric acid solution with a pH of 4, and then use absorbent paper to absorb the prepared hydrochloric acid solution until saturated. Lay one side of the electrode with a catalytic layer on both sides on the surface of the absorbent paper. After 1 hour, wash away the catalytic layer in contact with the hydrochloric acid to expose the alloy fiber, and then wash it with deionized water. After vacuum drying, an anion exchange membrane water electrolysis and oxygen evolution electrode is obtained.
[0032] Example 4 A method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode comprises the following steps: S1. The metal raw materials Ni, Fe, Cr, Mn, Mo, Zn and Al are weighed in a mass ratio of 95:1:0.5:0.5:2:0.5:0.5, and then put into a vacuum induction melting furnace to melt the metals and form a uniform alloy solution. The rods are formed through solidification, forging and rolling, and then cut into alloy fibers with a diameter of 20 μm. After the alloy fibers are dispersed, they are placed in a vacuum furnace with a degree of vacuum of 10 -4 The nickel fiber felt is sintered in a sintering furnace at 1000°C for 90 minutes, and then pressed at 20 MPa at room temperature to form a high-strength porous metal carrier, namely nickel fiber felt. The nickel fiber felt has a thickness of 0.2 mm and a porosity of 60%.
[0033] S2. Dissolve 10g of ferric chloride, 10g of cobalt chloride and 60g of nickel chloride in 2L of water, stir until mixed evenly to obtain a mixed solution; use nickel fiber felt as a carrier, place the carrier in the mixed solution, add 0.1mol / L potassium hydroxide solution to the mixed solution, and let it stand to react for 2h, then remove the nickel fiber felt, place it in clean water for ultrasonic cleaning 3 times, and vacuum dry to obtain an electrode with a catalytic layer on both sides.
[0034] S3. Use a pipette to measure 8.33 μL of concentrated hydrochloric acid, add deionized water to dilute it, and then introduce it into a 1 L volumetric flask to make up the volume. Prepare a hydrochloric acid solution with a pH of 4, and then use absorbent paper to absorb the prepared hydrochloric acid solution until saturated. Lay one side of the electrode with a catalytic layer on both sides on the surface of the absorbent paper. After 10 minutes, wash away the catalytic layer in contact with the hydrochloric acid to expose the alloy fiber, and then wash it with deionized water. After vacuum drying, an anion exchange membrane water electrolysis and oxygen evolution electrode is obtained.
[0035] Example 5 A method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode comprises the following steps: S1. The metal raw materials Ni, Fe, Cr, Mn, Mo, Zn and Al were weighed in a mass ratio of 95:1:0.5:0.5:2:0.5:0.5, and then put into a vacuum induction melting furnace to melt the metals and form a uniform alloy solution. The rods were solidified, forged and rolled, and then cut into fibers with a diameter of 20 μm. After the fibers were dispersed, they were placed in a vacuum furnace with a degree of vacuum of 10 -4 The nickel fiber felt was sintered in a sintering furnace at 1000°C for 90 minutes to form a nickel fiber felt with a thickness of 0.2 mm.
[0036] S2. Dissolve 12g of ferric chloride, 8g of cobalt chloride and 45g of nickel chloride in 2L of water, stir until mixed evenly to obtain a mixed solution; select nickel fiber felt with a thickness of 0.2mm and a porosity of 60% as a carrier, place the carrier in the mixed solution, then add 0.05mol / L potassium hydroxide solution to the mixed solution, and react for 5h, then remove the nickel fiber felt, place it in clean water for ultrasonic cleaning 3 times, and vacuum dry to obtain an electrode with a catalytic layer on both sides.
[0037] S3. Use a pipette to measure 8.33 μL of concentrated hydrochloric acid, dilute it with deionized water, and then introduce it into a 1 L volumetric flask to make up the volume. Prepare a hydrochloric acid solution with a pH of 4, and then use absorbent paper to absorb the prepared hydrochloric acid solution until it is saturated. Lay one side of the electrode with a catalytic layer on both sides on the surface of the absorbent paper. After 5 hours, wash away the catalytic layer in contact with the hydrochloric acid to expose the alloy fiber, then wash it with deionized water and vacuum dry it to obtain an anion exchange membrane water electrolysis and oxygen evolution electrode.
[0038] Example 6 A method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode comprises the following steps: S1. Weigh the metal Ni, Fe, Cr, Mn and Mo raw materials according to the mass ratio of 95:1:1:1:2, and then put them into a vacuum induction melting furnace to melt the metals and form a uniform alloy solution. After solidification, forging and rolling, they are formed into rods, which are then cut into alloy fibers with a diameter of 40 μm. After the alloy fibers are dispersed, they are placed in a vacuum furnace with a degree of vacuum of 10 -3 The nickel fiber felt is sintered in a sintering furnace at 1200°C for 30 minutes, and then pressed at 5 MPa at room temperature to form a high-strength porous metal carrier, namely nickel fiber felt. The nickel fiber felt has a thickness of 1 mm and a porosity of 70%.
[0039] S2. Dissolve 12g of ferric chloride and 8g of cobalt chloride in 2L of water, stir until the mixture is uniform, and obtain a mixed solution; use nickel fiber felt as a carrier, place the carrier in the mixed solution, add 0.001mol / L potassium hydroxide solution to the mixed solution, and let it stand for 6h. Then, remove the nickel fiber felt, place it in clean water for ultrasonic cleaning 3 times, and vacuum dry it to obtain an electrode with a catalytic layer on both sides.
[0040] S3. Use a pipette to measure 8.33 μL of concentrated hydrochloric acid, dilute it with deionized water, and then introduce it into a 1 L volumetric flask to make up the volume. Prepare a hydrochloric acid solution with a pH of 4.5, and then use absorbent paper to absorb the prepared hydrochloric acid solution until it is saturated. Lay one side of the electrode with a catalytic layer on both sides on the surface of the absorbent paper. After 1 hour, wash away the catalytic layer in contact with the hydrochloric acid to expose the alloy fiber, then wash it with deionized water and dry it in vacuum to obtain an anion exchange membrane water electrolysis and oxygen evolution electrode.
[0041] Example 7 A method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode comprises the following steps: S1. Weigh the metal raw materials Ni, Fe, Cr, Zn and Al in a mass ratio of 95:1:1:1:2, and then put them into a vacuum induction melting furnace to melt the metals and form a uniform alloy solution. After solidification, forging and rolling, the rods are formed, and then cut into alloy fibers with a diameter of 50 μm. After the alloy fibers are dispersed, they are placed in a vacuum furnace with a degree of vacuum of 10 -5 The nickel fiber felt is sintered in a sintering furnace at 1100°C for 60 minutes, and then pressed at 10 MPa at room temperature to form a high-strength porous metal carrier, namely nickel fiber felt. The nickel fiber felt has a thickness of 0.5 mm and a porosity of 50%.
[0042] S2. Dissolve 12g of ferric chloride and 45g of nickel chloride in 2L of water, stir until the mixture is uniform, and obtain a mixed solution; use nickel fiber felt as a carrier, place the carrier in the mixed solution, add 10mol / L potassium hydroxide solution to the mixed solution, and let it stand for 1h. Then, remove the nickel fiber felt, place it in clean water for ultrasonic cleaning 3 times, and vacuum dry it to obtain an electrode with a catalytic layer on both sides.
[0043] S3. Use a pipette to measure 8.33 μL of concentrated hydrochloric acid, dilute it with deionized water, and then introduce it into a 1 L volumetric flask to make up the volume. Prepare a hydrochloric acid solution with a pH of 5, and then use absorbent paper to absorb the prepared hydrochloric acid solution until saturated. Lay one side of the electrode with a catalytic layer on the surface of the absorbent paper. After 1 hour, wash away the catalytic layer in contact with the hydrochloric acid to expose the alloy fiber, then wash it with deionized water and dry it in vacuum to obtain an anion exchange membrane water electrolysis and oxygen evolution electrode.
[0044] Examples 1 to 7 of the present invention all produced anion exchange membrane water electrolysis oxygen evolution electrodes with excellent electrochemical performance. The following is a study using the anion exchange membrane water electrolysis oxygen evolution electrode of Example 1 as an example. The specific research methods and results are as follows: Figure 1 The SEM electron microscope images of the anion exchange membrane water electrolysis oxygen evolution electrode are given. Among them, the left picture is the surface morphology of the catalytic layer, and the surface metal hydroxide is a flaky structure; the right picture is the surface morphology of the conductive layer, and the surface has no flaky structure, indicating that the catalytic layer has been washed away.
[0045] Figure 2 Polarization curves of anion exchange membrane water electrolysis oxygen evolution electrode in a three-electrode system are given. In the three-electrode system, the anion exchange membrane water electrolysis oxygen evolution electrode is used as the working electrode, the mercury oxide electrode is used as the reference electrode, the Pt sheet is used as the counter electrode, and 1 mol / L KOH solution is used as the electrolyte. Figure 2 This is the polarization curve in the three-electrode system, reflecting the overpotential of the anion exchange membrane water electrolysis oxygen evolution electrode. 10mA / cm 2 When the oxygen evolution overpotential is only 120mV (10mA / cm 2 The potential corresponding to the above is 1.35 V minus the standard potential 1.23 V). The overpotential of the conventional electrode in the prior art is above 200 mV. The lower the overpotential, the better the surface catalytic activity. This indicates that the anion exchange membrane water electrolysis oxygen evolution electrode of the present invention has excellent catalytic activity.
[0046] Figure 3 Polarization curves for the double-sided catalytic electrode and anion exchange membrane water electrolysis oxygen evolution electrode of Example 1 are shown in an electrolyzer. The electrolyzer is a two-electrode system, with the other electrode being a carbon paper electrode coated with 40 wt% Pt / C, the electrolyte being a 1 mol / L KOH solution, and the separator being an anion exchange membrane. Figure 3 This is the polarization curve for the double-sided catalytic electrode and the anion exchange membrane electrode in the electrolyzer, reflecting the electrolysis performance. The higher the current density, the lower the corresponding voltage, the lower the energy consumption of the electrolyzer and the higher the performance.
[0047] Table 1 shows the contact resistance, high-frequency impedance after stacking, surface resistance and current density of the anion exchange membrane water electrolysis oxygen evolution electrode of each embodiment of the present invention and the electrode with catalytic layers on both sides of Example 1.
[0048] Table 1 Comparison of electrochemical performance As shown in Table 1, the smaller the contact resistance, the smaller the high-frequency impedance and surface resistance after stacking, and the greater the electrolytic stack current density at a voltage of 1.9 V.
[0049] The electrode with catalytic layer on both sides is an electrode without conductive layer. Its contact resistance, high frequency impedance and surface resistance are larger than those of anion exchange membrane water electrolysis oxygen evolution electrode (with conductive layer). Under the same voltage, the current density is small, and the maximum current density can only reach 1A / cm 2 , indicating that the conductive performance is effectively improved by acid corrosion of the catalytic layer.
[0050] Obviously, those skilled in the art may make various modifications and variations to the present invention without departing from the spirit and scope of the present invention. Thus, if such modifications and variations fall within the scope of the claims and their equivalents, the present invention is intended to include such modifications and variations.
Claims
1. A method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode, characterized in that: The steps include: The metal mixture is used as raw material, and is sequentially smelted, cooled, forged, rolled, cut into alloy fibers, made into felt, sintered at high temperature, and pressed into shape to obtain a high-strength porous metal carrier; The metal mixture is composed of Ni and an active metal raw material, the active metal raw material is selected from one or more of Fe, Cr, Mn, Mo, Zn, and Al; and the mass percentage of Ni in the metal mixture is ≥95%; Two or more soluble metal salts are dissolved in water to obtain a mixed solution; a high-strength porous metal support is immersed in the mixed solution, and then an alkaline solution is added and aged. The alkaline solution then converts the soluble metal salts into metal hydroxides, which grow on the surface of the high-strength porous metal support. The support is then washed with water until neutral, thereby obtaining an electrode with a catalytic layer on both sides. The catalytic layer on one side of the electrode having catalytic layers on both sides is cleaned with acid solution to expose the alloy fibers, thereby obtaining an anion exchange membrane water electrolysis oxygen evolution electrode.
2. The method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode according to claim 1, wherein: The diameter of the alloy fiber is 20μm~50μm.
3. The method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode according to claim 1, wherein: The conditions for high temperature sintering are: vacuum degree of 10 -3 ~10 -5 Under Pa conditions, sinter at 800℃~1200℃ for 30min~120min.
4. The method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode according to claim 1, wherein: The soluble metal salt is selected from soluble iron salt, soluble cobalt salt or soluble nickel salt, and the concentration of the soluble metal salt is 0.001 mol / L-1 mol / L.
5. The method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode according to claim 1, wherein: The alkali in the alkali solution is selected from one of KOH, NaOH, K2CO3, Na2CO3, KHCO3, NaHCO3, and urea, and the concentration of the alkali solution is 0.001mol / L-10mol / L.
6. The method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode according to claim 1, characterized in that: The porosity of the high-strength porous metal carrier is 50%~70% and the air permeability is 0.1cm 3 / (cm 2 ·s·kPa)~5cm 3 / (cm 2 ·s·kPa), thickness is 0.2mm~1mm.
7. The method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode according to claim 1, characterized in that: The aging conditions are: standing at room temperature for 1h~6h.
8. The method for preparing an anion exchange membrane water electrolysis oxygen evolution electrode according to claim 1, characterized in that: The acid in the acid solution is selected from one or more of oxalic acid, nitric acid, hydrochloric acid, and sulfuric acid, and the pH of the acid solution is 4-5.
9. An anion exchange membrane water electrolysis oxygen evolution electrode, characterized in that Prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the anion exchange membrane water electrolysis oxygen evolution electrode according to claim 9 in preparing an anion exchange membrane electrolyzer.